Interface Design of SnO2@PANI Nanotube With Enhanced Sensing Performance for Ammonia Detection at Room Temperature - Jia, Anqiang; Liu, Bitao; Liu, Haiyan; Li, Qiufeng; Yun, Yingxia (Frontiers in Chemistry, 2020)
Gas sensors with excellent stability and a high response at room temperature has drawn a great deal of attention and demand for them is huge. Surface designs provide inspiration toward making more useful sensor devices. The facile electrospinning process and Ar plasma treatment are used to fabricate rich and stable oxygen vacancies that contain a core-shell structured SnO2 polyaniline (PANI) nanotube. It shows that the induced surface oxygen vacancies would accelerate the PANI shell to generate more protons, which can enhance its sensor responsibility through reacting with the target Ammonia (NH3) gas. It was also found that the obtained oxygen vacancies can be well-protected by the coated PANI shell, which enhance and stabilize the gas response. It shows that the room temperature for the gas response of NH3 can reach up to 35.3 at 100 ppm. Finally, its good stability is demonstrated by the response-recovery performances carried out over 3 months and multiple cycles. This work indicates that this well-designed PANI-coated plasma-treated SnO2 is a potential way to design ammonia gas sensors.